Factors Associated with Doctor Satisfaction at Pondok Kopi Jakarta Islamic Hospital in 2021 - Yanti, Fitri; Rachmawati, Emma; Saputra, Hermawan (Journal of Health Policy and Management, 2024)
Background: Until now, doctor satisfaction has never been thoroughly measured at RSIJ Pondok Kopi. Based on the report of the Pondok Kopi RSIJ Medical Committee, there has been an increase in the number of doctor resignations from 2019 to 2021. This study aims to analyze factors related to doctor satisfaction at Pondok Kopi RSIJ.Subjects and Methods: in this study, the Mix Method with a Cross Sectional design, where data collection was carried out using questionnaires and in-depth interviews as the instruments. The sample used in this study were 74 respondents who were doctors at RSIJ Pondok Kopi.Results: This study showed that out of 74 respondents there were 38 doctors (51.4%) who were satisfied, and 36 doctors (48.6%) who were dissatisfied. Bivariate results show that all variables have a relationship with doctor satisfaction. The results of the multivariate analysis also found that the dominant variable was the doctor's level of commitment with Odds Ratio = 18.730 (CI = 2.525-138.914), which means that doctors who have a bad commitment have a risk of 18.730 times the chance of assessing dissatisfaction.Conclusion: Researchers recommend further intervention and control of hospital management to fulfill doctors' rights and obligations, so as to increase doctor satisfaction. Keywords: Job Satisfaction, Health Service Compensation, Work Environment